Impact of radiotherapy on bone health in women with rectal cancer – A prospective cohort study. Issue 12 (December 2022) - Svanström Röjvall, Annika; Buchli, Christian; Sääf, Maria; Magnusson, Per; Flöter Rådestad, Angelique; Martling, Anna; Segelman, Josefin
Abstract: Introduction: Pelvic radiotherapy (RT) increases the risk of pelvic insufficiency fractures. The aim was to investigate if RT is associated with changes in serum bone biomarkers in women with rectal cancer, and to examine the incidence of radiation-induced bone injuries and the association with bone biomarkers. Material and methods: Women diagnosed with rectal cancer stage I-III, planned for abdominal surgery ± preoperative (chemo) RT, were prospectively included and followed one year. Serum bone biomarkers comprised sclerostin (regulatory of bone formation), CTX (resorption), BALP and PINP (formation). A subgroup was investigated with annual pelvic magnetic resonance imaging (MRI). The association between RT and bone biomarkers was explored in regression models. Results: Of 134 included women, 104 had surgery with preoperative RT. The formation markers BALP and PINP increased from baseline to one year in the RT-exposed group ( p  < 0.001, longitudinal comparison). In the adjusted regression analysis, the mean increase in PINP was higher in the RT-exposed than the unexposed group (17.6 (3.6–31.5) μg/L, p  = 0.013). Sclerostin and CTX did not change within groups nor differed between groups. Radiation-induced injuries were detected in 16 (42%) of 38 women with available MRI. At one year, BALP was higher among women with than without bone injuries ( p  = 0.018, cross-sectional comparison). Conclusions: Preoperative RT was associated with an increase in the formation marker PINP, which could represent bone recovery following RT-induced injuries, commonly observed in participants evaluated with MRI. These findings should be further explored in larger prospective studies on bone health in rectal cancer patients.